Enhancement of Full Coverage Markov Model for Diverse Systems with Common Cause Failures - Dogruguven, Ersin H.; Ustoglu, Ilker (IEEE, 2018)
Development of mission critical safety systems requires much effort as the resulted system will have impacts on the human life, property and environment. The design criteria such as data interchange between CPUs, synchronization, computation speed and diagnostic measures shall exhaustively be evaluated along with the effects of the parameters used in the reliability and safety calculations ex tunc. This study focuses on the average frequency of a dangerous failure of the safety function (PFHG). In comparison to formulas provided in IEC 61508, a comprehensive and innovative Markov model is proposed for diverse architecture, which helps to cover different safety relevant states to get quantitative results more correctly than provided in the standards and previous studies. The proposed model is applied to the vital computer to be used in the railway domain for CBTC metro and ERTMS ETCS systems and compared with the current models.
Keywords: functional safety; PFHG; IEC 61508; Markov; CCF; SIL; CBTC; ERTMS ETCS; Automation & Control Systems; Computer Science; Engineering